1971
DOI: 10.1042/bj1220267
|View full text |Cite
|
Sign up to set email alerts
|

The rate-limiting step of protein synthesis in vivo and in vitro and the distribution of growing peptides between the puromycinlabile and puromycin-non-labile sites on polyribosomes

Abstract: 1. At 3 min after an intravenous injection of radioactive amino acids into the rat, the bulk of radioactivity associated with liver polyribosomes can be interpreted as growing peptides. 2. In an attempt to identify the rate-limiting step of protein synthesis in vivo and in vitro, use was made of the action of puromycin at 0 degrees C, in releasing growing peptides only from the donor site, to study the distribution of growing peptides between the donor and acceptor sites. 3. Evidence is presented that all grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1972
1972
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Beneficial effects of slow protein digestion in terms of sparing body protein mass may be attributed to a sustained amino acid delivery to the peripheral circulation, as slow protein uptake (casein, whey protein in repeated meals) resulted in a moderate and prolonged plasma hyperaminoacidemia compared to fast protein (free amino acid, whey protein in one meal) ( 22 ). Conversely, fast protein ingestion would induce a strong and transient amino acid delivery after ingestion ( 23 ), whereas only a part of these amino acids could be deposited as protein since intracellular amino acid concentration outreached the maximum for processing protein synthesis ( 24 ), and the surplus amino acids would be catabolized in the splanchnic bed as energy source. Soy protein, which can be rapidly digested and absorbed, would preferably be locally catabolized (up to 30%) after uptake by human, which results in higher urea production, and limit the peripheral accretion of soybean proteins (down to –20%) compared to milk protein which has a slower digestion rate ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Beneficial effects of slow protein digestion in terms of sparing body protein mass may be attributed to a sustained amino acid delivery to the peripheral circulation, as slow protein uptake (casein, whey protein in repeated meals) resulted in a moderate and prolonged plasma hyperaminoacidemia compared to fast protein (free amino acid, whey protein in one meal) ( 22 ). Conversely, fast protein ingestion would induce a strong and transient amino acid delivery after ingestion ( 23 ), whereas only a part of these amino acids could be deposited as protein since intracellular amino acid concentration outreached the maximum for processing protein synthesis ( 24 ), and the surplus amino acids would be catabolized in the splanchnic bed as energy source. Soy protein, which can be rapidly digested and absorbed, would preferably be locally catabolized (up to 30%) after uptake by human, which results in higher urea production, and limit the peripheral accretion of soybean proteins (down to –20%) compared to milk protein which has a slower digestion rate ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results may be compared with a number of other observations made on intact mammalian cells under normal and abnormal conditions. Earl & Hindley (1971) concluded that aminoacyl-tRNA is freely available in the liver of starved, diabetic or hypophysectomized rats, as well as in muscle of normal rats, and that neither the rate of binding of aminoacyl-tRNA nor that of translocation is ratelimiting. Similarly, it seems that elongation factor 2 cannot be the rate-limiting factor in mammalian cell protein synthesis in culture, since there is a lag between the initial elongation factor 2 depletion during diphtheria intoxication and the onset of a decreased rate of cellular protein synthesis (Gill et al, 1969).…”
Section: Discussionmentioning
confidence: 99%
“…A difference in the relative amount of peptidyl-tRNA located at the 'A' (acceptor) and 'P' (donor) sites of the ribosome would also be expected to alter the extent to which aminoacyl-tRNA is enzymically retained by ribosomes on Millipore filters. Although the findings of Earl & Hindley (1971) do not support the latter possibility, use of the puromycin reaction for the determination of the distribution of peptidyl-tRNA between the P and A sites (Skogerson & Moldave, 1968;Baliga et al, 1970) should help to resolve this question.…”
Section: Sources Ofmentioning
confidence: 92%
“…The capacity of salt-washed ribosomes prepared from the low-protein groups to bind aminoacyl-tRNA, in the presence of transferase I, was about half of that for ribosomes from control rats, although as discussed above, the capacity of the ribosomes for amino acid polymerization did not differ to this extent. This discrepancy may be explained in several, though not mutually exclusive, ways; it is possible that the binding of aminoacyl-tRNA is not rate limiting in the overall elongation-phase polypeptide synthesis in vitro (Earl & Hindley, 1971). Further, studies with ribosomes from muscle of diabetic rats (Castles et al, 1971) suggest that the binding of phenylalanyl-tRNA by ribosomes at low Mg2+ concentrations was diminished to a greater extent than was the synthesis of polyphenylalanine by the ribosome preparations.…”
Section: Sources Ofmentioning
confidence: 99%